AN ANALYSIS OF ENGLISH LEXICO-GRAMMATICAL FEATURES OF STUDENT’S DESCRIPTIVE TEXTS AT NORTH SULAWESI ACADEMY AND THEIR IMPLICATION FOR TEFL - Neman, Meily Ivane Esther (11th International Scholars Conference, 2016)
This study aims at: (1) identifying the lexico-grammatical features of descriptive text, (2) describing the grammaticality extent in reference to clause rank expression, and (3) elaborating the further implication of functional grammar for TEFL. The subjects of this research were 20 students of the eleventh grade of North Sulawesi Academy. The data were collected from students’ written descriptive texts. The results of the research are as follows. (1) The features of transitivity that are used by the students most prominently are relational processes. (2) The features of mood system are typically declarative. (3) The features of theme that is most prominently used by the students are unmarked clauses. (4) In terms of formal grammar, the students make some errors in writing forms of possessive noun and pronoun, the use of verb and linking verb, and also singularity and plurality of expressions. (5) as the pedagogical implications for TEFL, this research helps the teachers to improve the quality of teaching English, and to help the students to construct a good literacy